The Correlation between Digital Literacy Skills’ Level and Frequency of Digital Media Use in ELT Classroom - Anis Zayyana (Edulitics (Education, Literature, and Linguistics) Journal, 2023)
In this digital era, the era of a digital-dependent society, English teachers have to possess digital literacy skills (locating and consuming digital contents, creating digital contents, communicating digital contents) apart of master English language skills and pedagogical skills. The level of English teachers’ digital literacy skills is assumed to correlate to the frequency of digital media they used in ELT classes. Thus, to prove that assumption, the researcher conducted this study using a correlational research design. Self-assessment questionnaires were distributed to 24 English teachers in several regions in East Java. Then, the results showed that there was a significant correlation between the level of digital literacy skills and the frequency of digital media use in ELT classes. It leads to the conclusion that the higher the level of digital literacy, the more frequent digital media use in ELT classrooms. Knowing this, improving English teachers’ level of digital literacy skills matters